2002
DOI: 10.1128/jb.184.16.4630-4635.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Profiling in a Histidine Kinase Mutant of Helicobacter pylori Identifies Members of a Regulon

Abstract: To identify putative members of a regulon controlled by the H. pylori sensory histidine kinase HP0164 (HK0164), we constructed HK0164 null mutant H. pylori strains and analyzed bacterial gene transcription using DNA arrays. Seven genes were differentially expressed in multiple HK0164 mutant strains compared to their expression in control strains. Strain-dependent variations in differential expression were also detected. These results indicate that the signal transduction circuit utilizing HK0164 controls the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 17 publications
3
52
0
Order By: Relevance
“…The observation that the histidine kinase gene hp165 is not essential suggests that there are two sets of target genes of HP166; one group is essential for viability and is controlled by unphosphorylated HP166, while the second group is nonessential and is regulated by the phosphorylated response regulator (HP166ϳP). Target genes whose regulation requires HP166ϳ P have been identified previously (10,12,32). In this study we demonstrated by genetic complementation that the essential function of HP166 can be provided by a mutated response regulator derivative which is not capable of phosphorylation.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The observation that the histidine kinase gene hp165 is not essential suggests that there are two sets of target genes of HP166; one group is essential for viability and is controlled by unphosphorylated HP166, while the second group is nonessential and is regulated by the phosphorylated response regulator (HP166ϳP). Target genes whose regulation requires HP166ϳ P have been identified previously (10,12,32). In this study we demonstrated by genetic complementation that the essential function of HP166 can be provided by a mutated response regulator derivative which is not capable of phosphorylation.…”
mentioning
confidence: 82%
“…The NtrC-like response regulator HP703 controls the transcription of genes encoding components of the flagellar basal body and hook and the minor flagellin FlaB (35). In response to an acidic pH HP166 regulates the expression of the urease genes and of several genes encoding H. pylori-specific proteins with unknown functions (10,12,32). On the basis of in vitro DNA-binding experiments, it was hypothesized that HP1043 regulates its own expression, as well as transcription of the tlpB gene encoding a methyl-accepting chemotaxis protein (9).…”
mentioning
confidence: 99%
“…These two strains, both from Caucasian males, are closely matched in DNA sequences flanking the ins180 site, which suggested that this element might be a useful marker for distinguishing different types of strains. In addition, jhp0152 and the downstream jhp0151 genes are coexpressed from a single promoter (10,17), and ins180 is approximately 125 bp upstream of the transcriptional start site of jhp0152. We hypothesize that ins180 may introduce or disrupt a cis-acting sequence that affects downstream gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome transcriptional profiling of H. pylori strains cultured in low pH conditions identified more than 100 genes that were differentially expressed in the wild-type strain compared with an ArsS-deficient mutant (17). Transcriptional profiling of H. pylori cultured in neutral pH conditions identified a smaller number of genes that were differentially expressed in the wild-type and ArsS null mutant strains (26). Acid-responsive H. pylori genes that are differentially expressed in wild-type and arsS mutant strains include amidases (amiE, amiF) and members of the urease gene cluster (ureA, ureB, ureE, ureF, ureG, ureH, and ureI) (9, 10, 16 -18).…”
mentioning
confidence: 99%
“…A second set of genes in the ArsR regulon is not required for cell viability, and the regulation of these genes occurs by a pathway involving a phosphorylated form of ArsR (i.e. requiring the cognate histidine kinase, ArsS) (13,17,18,20,26,29 …”
mentioning
confidence: 99%